Pengembangan Media Pembelajaran Game Edukasi Berbasis Adobe Flash Pada Materi Operasi Hitung Campuran Sekolah Dasar - Apriana, Dina; Kudsiah, Musabihatul; alwi, Mijahamuddin; Hakim, Arif rahman; Firdaus, Anugerah (Publikasi Pendidikan, 2023)
This development research aims to describe the steps to develop learning media for educational games based on Adobe Flash in the mixed arithmetic operation material for grade IV elementary schools that meet the criteria of validity, practicality and effectiveness. This research is a type of research and development (Research and Development), the steps are guided by the ADDEI model, namely: (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5)Evaluation. The subjects of this study were 12 fourth grade students of SDN 5 Bungtiang. The instrument used to measure the validity of the Learning Media that was developed was an assessment questionnaire by material experts and media experts, to measure the practical aspects of the Adobe Flash-based Educational Game Learning Media. The validity of the Learning Media is assessed from the expert's assessment with a maximum score of 4 for each statement of the material expert getting a 90% ideal percentage and the media expert gets an ideal percentage of 87.5% which means valid, while the student response questionnaire to the Adobe Flash-Based Educational Game Learning Media gets a percentage ideal of 61% which means that it is interesting and the learning media for the Adobe Flash-based Educational Game developed are suitable for use in the learning process.